2022
DOI: 10.1021/acs.nanolett.2c02982
|View full text |Cite
|
Sign up to set email alerts
|

Facet Engineering for Amplified Spontaneous Emission in Metal Halide Perovskite Nanocrystals

Abstract: Auger recombination and thermalization time are detrimental in reducing the gain threshold of optically pumped semiconductor nanocrystal (NC) lasers for future on-chip nanophotonic devices. Here, we report the design strategy of facet engineering to reduce the gain threshold of amplified spontaneous emission by manyfold in NCs of the same concentration and edge length. We achieved this hallmark result by controlling the Auger recombination rates dominated by processes involving NC volume and thermalization tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 71 publications
4
36
0
Order By: Relevance
“…Inspired by the recent success of facet engineering, we have studied the HC cooling dynamics in 6-, 12-, and 26-faceted polyhedral CsPbBr 3 NCs. Interestingly, our study revealed that 12-faceted dodecahedral NCs (d-CsPbBr 3 ) and 26-faceted rhombicuboctahedral NCs (r-CsPbBr 3 ) are coveted materials characterized by polaron-mediated slower cooling (up to ∼10 times) compared to that of their cubic counterpart (c-CsPbBr 3 ) of similar size. , Subsequently, with the help of a molecular system, we successfully harvested HCs before their thermalization, signifying the tremendous implications of surface engineering for device applications. …”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Inspired by the recent success of facet engineering, we have studied the HC cooling dynamics in 6-, 12-, and 26-faceted polyhedral CsPbBr 3 NCs. Interestingly, our study revealed that 12-faceted dodecahedral NCs (d-CsPbBr 3 ) and 26-faceted rhombicuboctahedral NCs (r-CsPbBr 3 ) are coveted materials characterized by polaron-mediated slower cooling (up to ∼10 times) compared to that of their cubic counterpart (c-CsPbBr 3 ) of similar size. , Subsequently, with the help of a molecular system, we successfully harvested HCs before their thermalization, signifying the tremendous implications of surface engineering for device applications. …”
mentioning
confidence: 97%
“…The past few years have witnessed the great promise of six-faceted ({110}, {002}) all-inorganic perovskite NCs (CsPbX 3 ; X = Br, Cl, I) in photovoltaic and optoelectronic applications. Their unique optical properties, such as near-unity photoluminescence quantum yields (PLQYs), narrow emission spectra, tunable photoluminescence (PL) in the visible region, long carrier diffusion length, etc., are keys to their massive success in several real applications such as displays, lasers, LEDs and solar cells. Despite the vast accomplishments, six-faceted cube NCs are not free from challenges; in fact, many of them are directly linked to the device’s performance. One such example is the rapid cooling (∼0.5–0.7 ps) of hot carriers (HCs) in cubic nanocrystals (NCs), a significant setback toward achieving a power conversion efficiency (PCE) of a theoretically predicted value (∼66%) or at least to a Shockley–Queisser limiting value (∼33%). , Extensive efforts have been put forward in slowing down the cooling in perovskite materials to a time scale slower than the time needed for the extractions of HCs. Such attempts proposed several phenomena, including acoustical–optical phonon upconversion, hot-phonon bottleneck, large-polaron formation, Auger heating, etc., were responsible for slow cooling in perovskite materials. , For instance, Fu et al and Wang et al have observed decelerated cooling in perovskite materials exploiting the Auger heating and synergetic effect of doped alkali cations (K + , Cs + , Rb + ) reducing the phonon bottleneck threshold.…”
mentioning
confidence: 99%
See 3 more Smart Citations